Manual of low/no-space agriculture -cum- family business gardens - Ranasinghe, T. T. (Resource Centres on Urban Agriculture and Food Security (RUAF Foundation), 2009)
The intention of the manual is to promote and impart simple ways of preparing creative cultivation structures, suitable for any surrounding, whether urban, periurban or rural with limited space and resources.